Inappropriate use of propranolol among medical and dental students at the University of Jordan: cross-sectional study - Taha, Hana; Awamleh, Suhib; Al Tayyeb, AbdelRahman; Samhouri, Salwa; Abbasi, Yousef; Alwaked, Lujaien; El Jaber, Aya; Massad, Raseel; Alkhaldi, Sireen M. (Frontiers in Medicine, 2025)
AimThis paper aimed to investigate the prevalence of beta-blocker inappropriate use specifically propranolol, among medical and dental students at the University of Jordan. It examined the patterns of Propranolol consumption for stress management including frequency of usage, dosage, side effects experienced as well as the respondents’ level of awareness about the risks associated with unsupervised propranolol use.MethodsCross-sectional study conducted at the University of Jordan in December 2024 and recruited 584 students (418 Medicine, 166 Dentistry). The data were analyzed using SPSS (version 27). Descriptive statistics were used to describe the sample, Pearson’s chi-squared test, fisher’s exact test, independent samples t-test and binary logistic regression model were used to identify the predictors of propranolol use. Statistical significance was set at a p-value ≤ 0.05.ResultsAmong the participants, 9.9% of the students reported using propranolol and 44% of the users learned about the medication through the recommendation of their friends and peers. Even though most students (74.1%) were aware of the potential risks of unsupervised propranolol use, still, 58.6% of the users took it without a prescription. The most common reasons for using propranolol were anxiety management (65.5%) and exam stress (60.3%). Most propranolol users (60.3%) noticed improvement in their academic performance and 36.2% of them experienced side effects such as dizziness and fatigue.ConclusionSelf-medication with propranolol among medical students to deal with academic anxiety carries serious risks. The findings of this research necessitate covering the potential hazards of self-prescription with beta-blockers within the curriculum of undergraduate medical and dental students. Moreover, there is a need for implementing student psychosocial support programs to improve their approach to managing stress and academic pressure.